2005
DOI: 10.1557/jmr.2005.0246
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Chemical Reaction and Brittle Fracture Found in Electroless Ni(P)/immersion gold–solder Interconnection

Abstract: Occurrence of brittle interfacial fracture at an electroless Ni(P)/immersion gold-solder joint has long been a serious problem not yet fully understood. In our previous report on the electroless Ni(P) [J. Mater. Res. 19, 2428], it was shown that crystallization of the Ni(P) film and growth of the Ni 3 SnP layer were accelerated after the intermetallic compound (IMC) spalling, and accurate failure locus of the brittle fracture due to so-called "IMC spalling induced microstructure degradation of the Ni(P) film" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 20 publications
1
22
0
1
Order By: Relevance
“…A number of papers demonstrated that with the thicker intermetallics, the solder joints tend to have a brittle failure mode, dependent on the detailed solder alloys composition. [13][14][15][16] Excessive growth of intermetallics can deteriorate solder joint ductility. For example, in thermal fatigue damage, where shear deformation dominates as a main factor, there are several failure modes, including intermetallics/solder failure and bulk solder failure, dependent on solder alloy composition.…”
Section: Resultsmentioning
confidence: 99%
“…A number of papers demonstrated that with the thicker intermetallics, the solder joints tend to have a brittle failure mode, dependent on the detailed solder alloys composition. [13][14][15][16] Excessive growth of intermetallics can deteriorate solder joint ductility. For example, in thermal fatigue damage, where shear deformation dominates as a main factor, there are several failure modes, including intermetallics/solder failure and bulk solder failure, dependent on solder alloy composition.…”
Section: Resultsmentioning
confidence: 99%
“…During initial reflowing, the entire Au layer on the Ni layer dissolved into the molten solder, and the Sn-58Bi solder formed a uniform and continuous Ni 3 Sn 4 IMC (chunk-shaped) at the solder/Ni interface. 20,21) In a previous work, we investigated the interfacial reactions and joint mechanical reliability of Sn58Bi solder with three surface finishes, OSP, ENIG, and ENEPIG. 22) In the study, we successfully identified the interfacial products during the reflow reaction.…”
Section: )mentioning
confidence: 99%
“…In addition, mechanical handling and board attachment processes can also create brittle failures at the ENIG-solder interface. Although a number of potential root causes have been proposed, including: (i) hyperactive corrosion of the Ni(P) film during the immersion Au plating process; 7 (ii) interfacial segregation of phosphorus; 8 (iii) Kirkendall voiding; 9 and (iv) Ni 3 SnP formation, 10 the mechanism(s) responsible for this failure mode is not yet fully understood. Furthermore, a more complex mechanism for joint embrittlement has been proposed for devices with an ENIG pad finish on one side of the solder joint and a Cu-pad finish on the other side of the joint.…”
Section: Introductionmentioning
confidence: 99%